Biomass-derived self-supported porous carbon membrane embedded with Co nanoparticles as an advanced electrocatalyst for efficient and robust hydrogen evolution reaction. (August 2020) - Min, Shixiong; Duan, Yan; Li, Yanan; Wang, Fang
Abstract: Powderous transition metal-based electrocatalysts have been widely studied for hydrogen evolution reaction (HER), but their practical application still remains challenging due to the tedious slurry-based electrode assembly process and unavoidable stability decay at high current density. Herein, a self-supported H2 evolution cathode based on pomelo peel (PP)-derived porous carbon (PPDC) membrane with embedded Co nanoparticles (Co@PPDC) is developed by direct carbonization of Co-adsorbed PP (Co 2+ -PP). Benefiting from the large surface areas, the abundant open and interconnected pores, the highly graphitic PPDC membrane, and the highly dispersed Co nanoparticles, the self-supported Co@PPDC electrode demonstrates superior electrocatalytic performance for HER in 1.0 M KOH solution, with overpotentials of 154 and 264 mV at current densities of 10 and 100 mA cm −2, respectively. In addition, owing to the good structural integrity, the Co@PPDC electrode exhibits an excellent cycling stability for 2000 cycles and a stable current density of ∼100 mA cm −2 at a constant overpotential of 265 mV over 12 h with a nearly 100% Faradaic efficiency (FE) and H2 production rate of 1.56 mmol h −1 . Therefore, this work provides a versatile and effective strategy for development of high-performance self-supported electrodes at low cost for large-scale H2 production from electrochemical water splitting. Graphical abstract: A biomass-derived self-supported porous carbon membrane embedded with Co nanoparticles (Co@PPDC) shows superior activity and stability towards electrocatalytic H2 evolution reaction. Image 1 Highlights: A biomass-derived porous carbon-based membrane electrode (Co@PPDC) was fabricated. The porous Co@PPDC membrane possesses rapid electron transfer and mass transport. Co nanoparticles embedded within PPDC membrane with high dispersion. Co@PPDC membrane electrode exhibits superior HER activity and stability in alkaline solution.